Human Macrophages Exhibit GM-CSF Dependent Restriction of Mycobacterium tuberculosis Infection via Regulating Their Self-Survival, Differentiation and Metabolism - Mishra, Abhishek; Singh, Vipul K.; Jagannath, Chinnaswamy; Subbian, Selvakumar; Restrepo, Blanca I.; Gauduin, Marie-Claire; Khan, Arshad (Frontiers in Immunology, 2022)
GM-CSF is an important cytokine that regulates the proliferation of monocytes/macrophages and its various functions during health and disease. Although growing evidences support the notion that GM-CSF could play a major role in immunity against tuberculosis (TB) infection, the mechanism of GM-CSF mediated protective effect against TB remains largely unknown. Here in this study, we report that human macrophages isolated from different donors varied in their ability to produce GM-CSF and that those with relatively higher levels of GM-CSF were able to survive significantly longer during M. tuberculosis infection in vitro. GM-CSF-dependent prolonged survival of human macrophages also correlated with decreased bacterial burden and increased expression of self-renewal/cell-survival associated genes such as BCL-2 and HSP27. Antibody-mediated depletion of GM-CSF in macrophages resulted in induction of apoptotic/necrotic cell death and a simultaneous decrease in autophagic flux. Additionally, protective macrophages against M. tuberculosis that produced more GM-CSF, induced a stronger granulomatous response and produced increased levels of IL-1, IL-12, and IL-10 and decreased levels of TNF-and IL-6 In parallel, macrophages isolated from the peripheral blood of active TB patients exhibited reduced capacity to control the intracellular growth of M. tuberculosis and produced significantly lower levels of GM-CSF. Remarkably, as compared to healthy controls, macrophages of active TB patients exhibited significantly altered metabolic state correlating with their GM-CSF secretion levels. Altogether, these results suggest that relative levels of GM-CSF produced by human macrophages plays a critical role in preventing cell death and maintaining a protective differentiation and metabolic state of the host cell against M. tuberculosis infection.